2019
DOI: 10.2478/arls-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Occurrence and Dietary Exposure to Total Aflatoxin and Fumonisins in Bread: A Major Breakfast Bakery Product in Nigeria

Abstract: Bread, which is a major breakfast food, has been documented to be susceptible to contamination by toxic fungi metabolites (mycotoxins) in various parts of the world. Total aflatoxins (AfT) and fumonisins (FB) are two important mycotoxins known for their ability to cause health damage to animals and humans when ingested through food over a long time. This study set out to determine the presence and level of these mycotoxins in bread produced and/or consumed within Lokoja, Kogi State, Nigeria. After extraction, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Globally in 2019, data from January to December showed the most prevalent mycotoxins were FUM (70%) and DON (68%) (BIOMIN World mycotoxin survey 2020). A 10-year survey by Gruber-Dorninger et al 2019 in SSA, reviewed an increased shift in prevalence in Fumonisins (72.6%); ZEN (52.2%) and DON (49.5%) amidst other emerging mycotoxins (Ladeira et al 2017 ; Chilaka et al 2018b ; Ojochenemi et al 2019 ; Ikeagwulonu et al 2020 ; Kebede et al 2020 ). Table 1 shows an update of mycotoxin contamination of some food and feed commodities in different locations across Nigeria.…”
Section: Mycotoxins Contamination Of Food and Feeds In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Globally in 2019, data from January to December showed the most prevalent mycotoxins were FUM (70%) and DON (68%) (BIOMIN World mycotoxin survey 2020). A 10-year survey by Gruber-Dorninger et al 2019 in SSA, reviewed an increased shift in prevalence in Fumonisins (72.6%); ZEN (52.2%) and DON (49.5%) amidst other emerging mycotoxins (Ladeira et al 2017 ; Chilaka et al 2018b ; Ojochenemi et al 2019 ; Ikeagwulonu et al 2020 ; Kebede et al 2020 ). Table 1 shows an update of mycotoxin contamination of some food and feed commodities in different locations across Nigeria.…”
Section: Mycotoxins Contamination Of Food and Feeds In Nigeriamentioning
confidence: 99%
“…Stored ground melons are could be contaminated by mycotoxin due to their exposure to environmental factors that favours growth of fungi. Bread a major breakfast product in many parts of Africa, especially in Nigeria was confirm across various states in Nigeria to contain aflatoxin beyond the safe limit by Ojochenemi et al ( 2019 ). Onyedum et al ( 2020 ), reported 100% occurrence of aflatoxin contamination in millet, sorghum and yam flour at a range (4.80–248.20 μg/kg) beyond the safe limit of 4 μg/kg set by Commission of the European Communities (CEC).…”
Section: Mycotoxins Contamination Of Food and Feeds In Nigeriamentioning
confidence: 99%